2017
DOI: 10.3390/e19090466
|View full text |Cite
|
Sign up to set email alerts
|

Novel Early EEG Measures Predicting Brain Recovery after Cardiac Arrest

Abstract: Abstract:In this paper, we propose novel quantitative electroencephalogram (qEEG) measures by exploiting three critical and distinct phases (isoelectric, fast progression, and slow progression) of qEEG time evolution. Critical time points where the phase transition occurs are calculated. Most conventional measures have two major disadvantages. Firstly, to obtain meaningful time-evolution over raw electroencephalogram (EEG), these measures require baseline EEG activities before the subject's injury. Secondly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…32,45 Using subband entropy of EEG, we also uncovered that in rats subjected to 7-min ACA, continuous EEG activity began to return at approximately 15-20 min after resuscitation. 46 In this present study, we found EEG activity (represented by entropy as well as gamma band power) surged over 15-30 min post-ROSC, and this recovery of EEG activity is linked to better neurological outcomes. These results are consistent with our previous findings.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…32,45 Using subband entropy of EEG, we also uncovered that in rats subjected to 7-min ACA, continuous EEG activity began to return at approximately 15-20 min after resuscitation. 46 In this present study, we found EEG activity (represented by entropy as well as gamma band power) surged over 15-30 min post-ROSC, and this recovery of EEG activity is linked to better neurological outcomes. These results are consistent with our previous findings.…”
Section: Discussionsupporting
confidence: 52%
“…Entropy, as a mathematical measure of randomness of EEG patterns, has been utilized to monitor injury and recovery since lower entropy values were seen in pathological EEG patterns after CA 32,45 . Using subband entropy of EEG, we also uncovered that in rats subjected to 7‐min ACA, continuous EEG activity began to return at approximately 15–20 min after resuscitation 46 . In this present study, we found EEG activity (represented by entropy as well as gamma band power) surged over 15–30 min post‐ROSC, and this recovery of EEG activity is linked to better neurological outcomes.…”
Section: Discussionmentioning
confidence: 95%